2020
DOI: 10.1029/2020jc016403
|View full text |Cite
|
Sign up to set email alerts
|

Observed Variability of the North Atlantic Current in the Rockall Trough From 4 Years of Mooring Measurements

Abstract: The Rockall Trough is one of the main conduits for warm Atlantic Water to the Nordic Seas. Ocean heat anomalies, originating from the eastern subpolar gyre, are known to influence Arctic sea ice extent, marine ecosystems, and continental climate. Knowledge of the transport through this basin has previously been limited to estimates from hydrographic sections which cannot characterize the intra-annual and multiannual variability. As part of the Overturning in the Subpolar North Atlantic Programme (OSNAP), a moo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
44
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(48 citation statements)
references
References 46 publications
2
44
2
Order By: Relevance
“…Recent observations from the Hebridean region reveal that decadal scale variability in the strength of the European Slope Current is, to first order, directly connected to that of the cyclonic subpolar gyre (SPG; and associated meridional density gradients) with a strong (weak) SPG associated with a strong (weak) slope current (Marsh et al., 2017). These observations support the idea that the European Slope Current is largely recruited from the eastern North Atlantic and is connected, north of ∼55°N (i.e., Rockall Trough), to the upper part of the NAC (the NAC being the eastern limb of the SPG) (Houpert et al., 2020; Lozier et al., 2019). Further south, in the central North Atlantic (∼46–53°N), the NAC flows eastward in three main branches with circulation pathways strongly constrained by the Mid‐Atlantic Ridge (MAR) (Daniault et al., 2016).…”
Section: Core Location and Hydrographic Settingsupporting
confidence: 73%
“…Recent observations from the Hebridean region reveal that decadal scale variability in the strength of the European Slope Current is, to first order, directly connected to that of the cyclonic subpolar gyre (SPG; and associated meridional density gradients) with a strong (weak) SPG associated with a strong (weak) slope current (Marsh et al., 2017). These observations support the idea that the European Slope Current is largely recruited from the eastern North Atlantic and is connected, north of ∼55°N (i.e., Rockall Trough), to the upper part of the NAC (the NAC being the eastern limb of the SPG) (Houpert et al., 2020; Lozier et al., 2019). Further south, in the central North Atlantic (∼46–53°N), the NAC flows eastward in three main branches with circulation pathways strongly constrained by the Mid‐Atlantic Ridge (MAR) (Daniault et al., 2016).…”
Section: Core Location and Hydrographic Settingsupporting
confidence: 73%
“…While Petit et al's (2019) transport estimate is highly accurate, it is from a single synoptic study in a region of high temporal variability (Sarafanov et al, 2012, Koman et al, 2020. The estimates from Koman et al (2020) are a time-mean calculation but using altimetry as a reference velocity may not fully resolve finer mesoscale features near topography, potentially resulting in an underestimate of velocity (Chafik et al, 2014;Pujol et al, 2016;Houpert et al, 2020;Koman et al, 2020). Koman et al (2020) also analyzed three OSNAP cruise sections along the Reykjanes Ridge and found that those synoptic realizations of the flow over the ridge varied widely (their Fig.…”
Section: Reykjanes Ridgementioning
confidence: 99%
“…1) propagates waters of subtropical origin into the gyre as part of the upper limb of the AMOC. These waters flow into the basin at two primary locations: a smaller buoyancy-driven current in the east confined to the flank of the continental shelf at depths < 1000 m, and a larger flow in the basin's interior (Houpert et al, 2020). Studies from the Extended Ellett Line program (Holliday et al, 2000;Holliday et al, 2015) found a net northward transport of 3-4 Sv of the upper AMOC through the Rockall Trough using a mid-depth level of no motion.…”
Section: Rockall Troughmentioning
confidence: 99%
See 2 more Smart Citations